2020
DOI: 10.1038/s41467-019-13777-z
|View full text |Cite
|
Sign up to set email alerts
|

Double layer charging driven carbon dioxide adsorption limits the rate of electrochemical carbon dioxide reduction on Gold

Abstract: Electrochemical CO 2 reduction is a potential route to the sustainable production of valuable fuels and chemicals. Here, we perform CO 2 reduction experiments on Gold at neutral to acidic pH values to elucidate the long-standing controversy surrounding the rate-limiting step. We find the CO production rate to be invariant with pH on a Standard Hydrogen Electrode scale and conclude that it is limited by the CO 2 adsorption step. We present a new multi-scale modeling scheme that integrates ab initio reaction kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
365
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(386 citation statements)
references
References 75 publications
20
365
0
1
Order By: Relevance
“…• Major differences between CHE and FGC calculations will occur for adsorbates with significant dipole moments, whenever the work function change per adsorbate is large. This is in line with other studies 30,40 and was noted early 7,98 . The improved description at the FGC level comes at a somewhat increased computational cost. This does not so much refer to the actual DFT calculations themselves, thanks to efficient implementations of current implicit solvation models.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…• Major differences between CHE and FGC calculations will occur for adsorbates with significant dipole moments, whenever the work function change per adsorbate is large. This is in line with other studies 30,40 and was noted early 7,98 . The improved description at the FGC level comes at a somewhat increased computational cost. This does not so much refer to the actual DFT calculations themselves, thanks to efficient implementations of current implicit solvation models.…”
Section: Discussionsupporting
confidence: 94%
“…The capabilities of FGC approaches have been highlighted in several publications and include a potential-dependence of chemical reaction steps 8,[29][30][31]39,40 , potential-induced surface reconstructions or shifts of stable adsorption sites 5,11,13,41 . However, there is presently still limited understanding of the methodological differences between the still prevalent zerocharge CHE and the variable-charge FGC approaches.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study, based on experiments and multiscale modeling, found that even the rate-limiting step is dependent on the applied potentials. [54] Thirdly, the oxidation state of Zn under the CO 2 RR, that is, the nature of the active sites, is not clear. By operando X-ray absorption fine-structure spectroscopy measurements, Jeon et al [43] demonstrated the coexistence of cationic Zn species and metallic Zn during the CO 2 RR.…”
Section: Electrochemical Characterizations and Product Analyses Of Thmentioning
confidence: 99%
“…This is especially true for CO 2 electroreduction on Au electrodes because weak CO adsorption leads to very low surface coverage during steady state turnover. 24,25 Consequently, this method answers a long-standing challenge in Au electrocatalysis, and promises to inform a variety of processes occurring at active electrochemical interfaces.…”
Section: Introductionmentioning
confidence: 99%